Search for molecular descriptors and computer prediction of biological activity in a series of S-derivatives (1,2,4-triazole-3(2H)-yl)methyl)thiopyrimidines - Karpenko, Yu. V.; Panasenko, O. I.; Litun, A. P. (Aktualʹnì pitannâ farmacevtičnoï ì medičnoï nauki ta praktiki, 2024)
Most pharmaceutical compounds interact with various molecular compositions in the body, leading to complex biological effects. Furthermore, during biotransformation, they may generate one or more metabolites with potent bioactive properties. Therefore, the development and careful use of new medications require thorough examination of their biological impact profiles, including considerations of human metabolic processes. In silico techniques are currently widely used to evaluate the interactions of emerging drug candidates with pharmacological conditions and predict their metabolic conversions. To investigate the bioactivity of compounds based on the structure of 1,2,4-triazole-3(2H)-thione with pyrimidine-2-thiol, we generated a combinatorial library of bioregulators using the computer programs SuperPred and SwissADME. The relevance of this research is underscored by the ongoing quest for novel biomolecular compounds that are highly effective yet low in toxicity, spanning both natural and synthetic sources. Much attention is directed towards nitrogen-containing heterocycles, particularly derivatives of 1,2,4-triazole, due to their substantial medical and biological potential. The aim of the work is to create a combinatorial library of bioregulators, which contains the structures of 1,2,4-triazole and pyrimidine, and to carry out in silico screening of heterocycle derivatives using the SuperPred web server to determine promising directions for the study of their bioactivity. Materials and methods. The subject of our research is S-derivatives of (1,2,4-triazole-3(2H)-yl)methyl)thiopyrimidines. Virtual screening of compounds was carried out using the SuperPred computer program. The ADME study was performed using the free service SwissADME, which is used to evaluate the pharmacokinetics, bioavailability, and interaction of small molecules with enzymes in medicinal chemistry. Results. Predicting the likelihood of a substance demonstrating a particular biological activity enables the selection of the most appropriate tests for studying the activity of a given chemical compound, as well as identifying which substances available to the researcher are most likely to enhance the effectiveness of the effects. This principle is grounded in the concept that “the biological activity of a substance is a function of its chemical structure”. Such predictions are generated based on the structural formula of a chemical compound and can be made during the planning stage of synthesis. Conclusions. A combinatorial library of bioregulators was created by combining the structure of 1,2,4-triazole-3(2H)-thione with pyrimidine-2-thiol. The conducted virtual screening of the 1,2,4-triazole-3(2H)-thione heterocycle with pyrimidine-2-thiol shows promise for obtaining non-toxic compounds with antineoplastic biological activity. Screening of derivatives, particularly S-derivatives of (1,2,4-triazole-3(2H)-yl)methyl)thiopyrimidines, indicates the potential for discovering biologically active substances with antineoplastic, antibacterial, analgesic, antidiabetic, antihypertensive, and other types of biological activities within this compound series.